Glyoxal and methylglyoxal in Atlantic seawater and marine aerosol particles: method development and first application during the Polarstern cruise ANT XXVII/4 - M. van Pinxteren; H. Herrmann (Atmospheric Chemistry and Physics, 2013)
An analytical method for the determination of the alpha dicarbonyls glyoxal (GLY) and methylglyoxal (MGLY) from seawater and marine aerosol particles is presented. The method is based on derivatization with o-(2,3,4,5,6-Pentafluorobenzyl)-hydroxylamine (PFBHA) reagent, solvent extraction and GC-MS (SIM) analysis. The method showed good precision (RSD < 10%), sensitivity (detection limits in the low ng L−1 range), and accuracy (good agreement between external calibration and standard addition). The method was applied to determine GLY and MGLY in oceanic water sampled during the Polarstern cruise ANT XXVII/4 from Capetown to Bremerhaven in spring 2011. GLY and MGLY were determined in the sea surface microlayer (SML) of the ocean and corresponding bulk water (BW) with average concentrations of 228 ng L−1 (GLY) and 196 ng L−1 (MGLY). The results show a significant enrichment (factor of 4) of GLY and MGLY in the SML. Furthermore, marine aerosol particles (PM1) were sampled during the cruise and analyzed for GLY (average concentration 0.19 ng m−3) and MGLY (average concentration 0.15 ng m−3). On aerosol particles, both carbonyls show a very good correlation with oxalate, supporting the idea of a secondary formation of oxalic acid via GLY and MGLY. Concentrations of GLY and MGLY in seawater and on aerosol particles were correlated to environmental parameters such as global radiation, temperature, distance to the coastline and biological activity. There are slight hints for a photochemical production of GLY and MGLY in the SML (significant enrichment in the SML, higher enrichment at higher temperature). However, a clear connection of GLY and MGLY to global radiation as well as to biological activity cannot be concluded from the data. A slight correlation between GLY and MGLY in the SML and in aerosol particles could be a hint for interactions, in particular of GLY, between seawater and the atmosphere.